Motivations for Developing Renewable Energy and Solar Energy : Panel Cointegration Approach - Damette, Olivier (DEMO, 2017)
The threats posed by global warming issues have prompted European governments to accelerate their energy transition and increase their electricity production from renewable energies (Renewable Energy). The deployment of renewables energy in Europe is however heterogeneous according countries and this growth of renewables is likely to be driven by some macroeconomic variables previously analysed in the literature (CO2 emissions, national income, energy consumption and energy dependency, oil price dynamics). In this article, we show using panel fixed effects estimator that econometric results outlined in the previous literature are robust using our new data set by considering all sources of renewables energy. However, we also show that previous papers seem to have neglected the presence of nonstationary and cointegration issues when we assess the relationship between renewables and its drivers. Using suitable cointegrating estimators (DOLS, FMOLS), we relativise the scope of the results usually identified in the literature. By conducting the same analysis for the particular case of solar energy, we show that this particular type of energy, as suggested by a scarce literature, does not react as strongly to the main macroeconomic determinants as the renewables energy as a whole. Panel estimates using fi xed eff ects and panel estimators adapted to the presence of cointegration lead to the same conclusion that only the level of energy dependency is really a major driver in the decision of the governments to produce solar energy.(original abstract)